Yield and must composition of grapevines subjected to phosphate fertilization in Southern Brazil - Schmitt, Djalma Eugênio; Borghezan, Marcelo; Ambrosini, Vítor Gabriel; Comin, Jucinei José; Trapp, Talita; Brunetto, Gustavo (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the yield and must composition of 'Cabernet Sauvignon' and 'Chardonnay' grapevines subjected to phosphorus applications to a soil from a high-altitude region of Southern Brazil, during three crop seasons. Experiments 1 and 2 were carried out in 'Cabernet Sauvignon' and 'Chardonnay' commercial vineyards, respectively, in the municipality of Água Doce, located in the Midwestern region of the state of Santa Catarina. The soil from the two vineyards was classified as a Typic Humicryept. The used source of P was triple superphosphate (45% P2O5). From 2011 to 2013, at flowering, a total of 0, 10, 20, 40, and 80 kg ha-1 P2O5 were applied in the crown projection area, to the soil surface, without incorporation, in both vineyards. Soil and leaf P concentration, yield parameters, and must quality were evaluated. The increase in P availability decreased total titratable acidity and tartaric acid in the must of the 'Cabernet Sauvignon' grapevine in the 2013/2014 crop season and increased pH and total soluble solids in the must of the 'Chardonnay' grapevine in the 2011/2012 crop season. Phosphorus application to the soil increases the levels of available phosphorus, but does not result in higher yields for 'Cabernet Sauvignon' and 'Chardonnay' grapevines.
Keywords: Vitis vinifera; available phosphorus; 'Cabernet Sauvignon'; 'Chardonnay'; high altitude